2018
DOI: 10.1128/aac.02326-17
|View full text |Cite
|
Sign up to set email alerts
|

Anidulafungin Pharmacokinetics in Ascites Fluid and Pleural Effusion of Critically Ill Patients

Abstract: Anidulafungin concentrations were quantified with high-pressure liquid chromatography (HPLC) and UV detection of the ascites fluid and pleural effusion of 10 adult critically ill patients. Samples were collected from ascites fluid and from pleural drains or during paracentesis and thoracentesis, respectively. Anidulafungin levels in ascites fluid (0.12 to 0.99 μg/ml) and in pleural effusion (0.32 to 2.02 μg/ml) were below the simultaneous levels in plasma (1.04 to 7.70 and 2.48 to 13.36 μg/ml, respectively) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…A recent study involving seven patients (Welte et al, 2018), reported anidulafungin concentrations in the range of 0.12-0.99 mg/l in ascitic fluid, which is consistent with the average obtained from the data in the present study.…”
Section: Resultssupporting
confidence: 93%
“…A recent study involving seven patients (Welte et al, 2018), reported anidulafungin concentrations in the range of 0.12-0.99 mg/l in ascitic fluid, which is consistent with the average obtained from the data in the present study.…”
Section: Resultssupporting
confidence: 93%
“…The levels obtained in PF in the current patients were similar to those obtained by other authors, and they confirmed a moderate penetration of echinocandins into the PF in patients with IAC. Perez-Civantos et al confirmed anidulafungin levels between 0.7-0.9 mg/mL, with an average AUC 0À24 of 57.9 mg  h/L, (Pérez Civantos et al, 2019) which was similar to the levels obtained by Welte et al (0.12-0.99 mg  h/mL) (Welte et al, 2018). Andes et al (2011) demonstrated that the AUC/MIC ratio, APACHE II score and history of corticosteroid use were significant independent predictors of a favourable response for all Candida species.…”
Section: Discussionsupporting
confidence: 70%
“…The low sensitivity of echinocandins to Candida parapsilosis (C. parapsilosis) and development of resistance, especially in Candida glabrata (C. glabrata) in patients receiving prolonged treatment with echinocandins have recently been the focus of diffusion studies on these antifungals at an intra-abdominal level (Grau et al, 2015;Pérez Civantos et al, 2019;Welte et al, 2018;Dupont et al, 2017;Sganga et al, 2019). Different pharmacokinetic/pharmacodynamic (PK/PD) studies have recently been published for echinocandins (Luque et al, 2019;Andes et al, 2011;Hall et al, 2013;Aguilar et al, 2014a;Aguilar et al, 2014b;Andes et al, 2010), but very few have focused on candidiasic peritonitis or intra-abdominal fungal infection.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, almost 20% of patients with IC broke through systemic prophylaxis, nearly always with micafungin. Micafungin breakthrough IFIs in the setting of invasive disease outside of the bloodstream raise the question of inadequate tissue penetration of echinocandins, particularly into the pleural space [33][34][35]. In addition, micafungin breakthroughs among patients requiring EMCO may also reflect decreased drug exposure related to micafungin extraction by the ECMO circuit [36].…”
Section: Discussionmentioning
confidence: 99%